2010
DOI: 10.1074/jbc.m110.115337
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Thrombin Bound to the Uncleaved Extracellular Fragment of PAR1

Abstract: Abundant structural information exists on how thrombin recognizes ligands at the active site or at exosites separate from the active site region, but remarkably little is known about how thrombin recognizes substrates that bridge both the active site and exosite I. The case of the protease-activated receptor PAR1 is particularly relevant in view of the plethora of biological effects associated with its activation by thrombin. Here, we present the 1.8 Å resolution structure of thrombin S195A in complex with a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 62 publications
(110 reference statements)
5
110
1
2
Order By: Relevance
“…The PAR3(44 -56) and PAR1(49 -62) sequences were shown previously by x-ray crystallography to interact with thrombin ABE I (35,36). In our HDX control studies, PAR3(44 -56) has not been observed to bypass ABE I and move on to bind ABE II.…”
Section: Probing Conformational Events After Abe I Binding-x-raymentioning
confidence: 60%
“…The PAR3(44 -56) and PAR1(49 -62) sequences were shown previously by x-ray crystallography to interact with thrombin ABE I (35,36). In our HDX control studies, PAR3(44 -56) has not been observed to bypass ABE I and move on to bind ABE II.…”
Section: Probing Conformational Events After Abe I Binding-x-raymentioning
confidence: 60%
“…The conceptual framework of the E*-E equilibrium extends to other classes of enzymes such as caspases and explains how small molecules can induce activation of the pro-enzyme (43) by stabilizing the E form. Prethrombin-2 exists in the E* and E forms (23,26) and carries a P1-P4 sequence in the activation domain that closely resembles that of PAR1, the most specific substrate of thrombin (44). What prevents autoactivation in prethrombin-2 is burial of Arg-15 in the activation domain, an unanticipated feature uncovered when the structure of this zymogen was solved for the first time in the free form (23).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there is not structural information on the binding sites of these PAR1 antagonists to be used for structure-based design of new antagonists. However, recent mutagenesis studies on thrombin and/or PAR1 [34][35][36][37][38][39][40][41][42], X-ray of thrombin crystallized with diverse N-terminal fragments of PAR1 [43,44], and NMR studies on the (Ala 26 -Hse 103 ) N-terminal sequence of PAR1 [45] have shown that the first thrombin/PAR1 interaction is produced between the exosite I of thrombin and the hirudin-like sequence of PAR1 (K 51 YEPF 55 ), and that this first interaction is essential and determinant for high affinity. It seems that the hydrophobic residues F34, I82, L65 and Y76, and the basic residues R67 and R73, of the exosite I of thrombin are important for high affinity.…”
Section: Introductionmentioning
confidence: 99%